Надвидовая систематика выхухолей рода Desmana (Insectivora, Talpidae) - Топачевский, В.А.; Пашков, А.В. (Вестник зоологии, 1983)
A superspecific system of the genus Desmana Giuld. is tentatively proposed on the basis of a comprehensive analysis of new palaeontological material obtained during two last decades for a number of Neogene-Anthropogene sites in Western and Eastern Europe. After dentition peculiarities, the following subgenera are established: Desmana s.str., Praedesmana subgen.n., Pliodesmana subgen.n., Archaeodesmana sub gen.n. and Galemodesmana subgen.n. Ii is possible that die fo further improvement of information available some of above subgenera will be advanced to generic rank level. Archaeodesmana, Praedesmana and Desmana are considered as a continuous phylogenetic succession, whereas Pliodesmana and Galemodesmana represent parallel branches, derived from common trunk at different levels of the phyletic development of the genus.